2012
DOI: 10.1161/strokeaha.112.652065
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis in Warfarin-Associated Intracranial Hemorrhage Despite Anticoagulation Reversal

Abstract: on behalf of the Canadian PCC Registry (CanPro) Investigators* Background and Purpose-Anticoagulant-associated intracranial hemorrhage (aaICH) presents with larger hematoma volumes, higher risk of hematoma expansion, and worse outcome than spontaneous intracranial hemorrhage. Prothrombin complex concentrates (PCCs) are indicated for urgent reversal of anticoagulation after aaICH. Given the lack of randomized controlled trial evidence of efficacy, and the potential for thrombotic complications, we aimed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 30 publications
(24 reference statements)
5
131
0
11
Order By: Relevance
“…Previously, Senft et al 25 and Taussky et al 30 analyzed a small cohort of patients with aSDH that occurred during OAT (11 and 16 patients) and showed no significant difference in functional outcome or mortality rate. In contrast, several previous studies observing anticoagulation in intracranial hemorrhage reported anticoagulation or antiplatelet treatment at the time of presentation as an important poor prognostic marker, 10,21,24,27,31 and one of the studies 20 reported a 1.7 times higher risk of mortality in patients on OAT at the time of the intracranial hemorrhage. In our study with a larger cohort of patients on OAT (n = 74), we observed similar results, with a clear significance toward unfavorable outcome and a mortality rate in the OAT group that was almost twice as high as that in the no-OAT group.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previously, Senft et al 25 and Taussky et al 30 analyzed a small cohort of patients with aSDH that occurred during OAT (11 and 16 patients) and showed no significant difference in functional outcome or mortality rate. In contrast, several previous studies observing anticoagulation in intracranial hemorrhage reported anticoagulation or antiplatelet treatment at the time of presentation as an important poor prognostic marker, 10,21,24,27,31 and one of the studies 20 reported a 1.7 times higher risk of mortality in patients on OAT at the time of the intracranial hemorrhage. In our study with a larger cohort of patients on OAT (n = 74), we observed similar results, with a clear significance toward unfavorable outcome and a mortality rate in the OAT group that was almost twice as high as that in the no-OAT group.…”
Section: Discussionmentioning
confidence: 73%
“…25,30 Although most of the experimental as well as clinical studies have shown the prognostic relevance of OAT in intracranial hemorrhage, the relationship between aSDH and OAT remains unclear. 10,13,30,35 In patients receiving OAT who suffer intracranial hemorrhage, first-line management is the reversal of anticoagulation, and the treatment differs depending on the OAT profile. The effectiveness of desmopressin and thrombocyte concentrate in patients treated with antiplatelet agents or prothrombin complex concentrates (PCC) in patients treated with a vitamin K antagonist has been reported in several studies and has recently been addressed in 2 systematic reviews.…”
mentioning
confidence: 99%
“…In addition to these disadvantages, warfarin carries the risk of intracranial hemorrhage which occurs in 0.4% of patients per year and has a mortality of approximately 50% [5][6][7]. Overall these disadvantages have resulted in apprehension in physicians' prescribing and patients' uptake of this medication.…”
Section: Health Systems and Policy Research Issn 2254-9137mentioning
confidence: 99%
“…While it has proven efficacy in treating and preventing thrombotic conditions (stroke and venous thromboembolism [VTE]), warfarin is also associated with several disadvantages such as frequent lab monitoring, multiple drug interactions, narrow therapeutic index and interpersonal variability in metabolism and target effect due to genetic polymorphisms [1][2][3][4][5][6][7]. These factors correlate to a 40-fold This article is available from: http://www.hsprj.com/archive.php…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from large cohorts of patients on VKA estimate the fatality rate of VKA-related major bleeding at ϳ15%-20%, up to 50% for intracranial bleeding. 22,23 Although there was no direct comparison with patients treated with VKA, it appears that rates of rivaroxaban-related major bleeding may be lower and outcomes are not worse than in VKA-treated patients. In summary, only small numbers of patients with rivaroxaban-associated bleeding required a reversal strategy, with prohemostatic therapy being given only in life-threatening situations.…”
Section: Do We Really Need Antidotes For Noacs?mentioning
confidence: 99%